2002
DOI: 10.1007/bf03165102
|View full text |Cite
|
Sign up to set email alerts
|

Idiopathic thrombocytopenic purpura: Pathophysiology and management

Abstract: Our understanding of the pathophysiology of ITP owes to pioneering work of W J Harrington in 1951, delineating the immunologic nature of platelet destruction. In ITP, antibody-coated platelets are destroyed by macrophages of RES. However, other mechanisms are also implicated: C-mediated platelet lysis and newly described C-independent peroxide injury. Both induce platelet fragmentation and lysis, generating procoagulant platelet microparticles (PMP). A third mechanism of platelet consumption in the microvascul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0
3

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 74 publications
0
20
0
3
Order By: Relevance
“…Mostly due to IgG auto body, which bind the platelet by itself. 13 Misdiagnosis of thrombocytopenia sometimes happen. In a research by Bader-Meunier et al, was found that children the suspected diagnosis on referral was autoimmune thrombocytophenic purpura and the final diagnosis was inherited thrombocytopenia.…”
Section: 4 Dental Management Of Thrombocytopeniamentioning
confidence: 99%
“…Mostly due to IgG auto body, which bind the platelet by itself. 13 Misdiagnosis of thrombocytopenia sometimes happen. In a research by Bader-Meunier et al, was found that children the suspected diagnosis on referral was autoimmune thrombocytophenic purpura and the final diagnosis was inherited thrombocytopenia.…”
Section: 4 Dental Management Of Thrombocytopeniamentioning
confidence: 99%
“…Consequently, they lead to thrombocytopenia and generally to bleeding diathesis (1,2). Nevertheless, ITP, even rare, may lead to thrombotic complications, including ischemic stroke (2,3). Herein, we reported a female case with ITP who developed cerebral infarction due to the thrombus in the middle cerebral artery (MCA).…”
Section: Introductionmentioning
confidence: 99%
“…In ITP, antibodies bind to platelet-specific antigens, and antibody-bound platelets are removed from circulation by splenic macrophages. Consequently, they lead to thrombocytopenia and generally to bleeding diathesis (1,2). Nevertheless, ITP, even rare, may lead to thrombotic complications, including ischemic stroke (2,3).…”
Section: Introductionmentioning
confidence: 99%
“…There are some reports regarding hepatotoxic effects of Danazol after more than 2 years of use, but no reports of adverse effects during short time periods [11,12].…”
Section: Introductionmentioning
confidence: 99%